Micro–Macro Mechanical Relations in Palmetto Wood by Numerical Homogenisation - Saavedra-Flores, E (Elsevier Ltd, 2016)
In this paper we investigate micro–macro mechanical relations in Palmetto wood, a natural composite, by means of a computational homogenisation-based multi-scale modeling approach. The homogenisation procedure is solved sequentially at multiple length scales by following a bottom-up approach. The proposed strategy consists of homogenising the three length-scales by means of representative volume elements of material. The resulting effective macroscopic properties allow us to compute the mechanical response of individual macro-fibres and bulk wood specimens by means of a standard finite element procedure. The numerical predictions are compared successfully with experimental measurements. Following the validation, a parametric study is performed to investigate the micro–macro relations in Palmetto wood. The influence of several micro-structural features present at different length scales are investigated, such as the cellulose content and its crystallinity, the microfibril angle, the cell-wall thickness of micro-fibres, and the porosity of macro-fibres and their surrounding matrix, among others. The effects of such microscopic parameters are investigated on the Young s modulus and density of Palmetto bulk wood. These results show that the present strategy can pave the way for further studies on complex microstructure–property relationships existing in different wood species, and on the possible development of more advanced bio-inspired composite materials. © 2016 Elsevier Ltd